Study the content of a bacterium Listeria monocytogenes of fatty acids - Ameera Alrawi; Mayada Altaee; Sahera Hameed (College of Education for Pure Sciences, 2007)
The study conducted the determination of fatty acids of Listeria monocytogenes by using Gas Liquid Chromatography (GLC) after extraction and esterification of fatty acids . From accounting the retention time of isolated fatty acids and comparison with standard fatty acids, the results showed domination of saturated types, Myristic acid ( 13.408%) Followed by Stearic acid (3.019%) among other saturated fatty acid while the unsaturated fatty acids, the Linoleic acid formed higher percent ( 4.591%) followed by Oleic acid (2.254%) . The other unsaturated fatty acids were differed in their percentages .